Specialization on Ficus Supported by Genetic Divergence and Morphometrics in Sympatric Host-Populations of the Camellia Aphid, Aphis aurantii - Li, Qiang; Chen, Cui; Wu, Yangxue; Siddiqui, Junaid Ali; Lu, Congcong; Cheng, Zhentao; Li, Yonghui; Liu, Qian; Huang, Xiaolei (Frontiers in Ecology and Evolution, 2021)
Adaptation to different host plants is considered to be an important driver of the divergence and speciation of herbivorous insects. The application of molecular data and integrated taxonomic practices in recent years may contribute to our understanding of population divergence and speciation, especially for herbivorous insects considered to be polyphagous. Aphis aurantii is an important agricultural and forestry pest with a broad range of host plants. In this study, samples of A. aurantii feeding on different host plants in the same geographical area were collected, and their population genetic divergence and morphological difference were analyzed. Phylogenetic analysis and haplotype network analysis based on five genes revealed that the population on Ficus exhibited significantly genetic divergence from populations on other host plants, which was also supported by the statistical analysis based on measurements of 38 morphological characters. Our results suggest that A. aurantii has undergone specialized evolution on Ficus, and the Ficus population may represent a lineage that is experiencing ongoing sympatric speciation.